Survey of Downy Mildew Disease of Maize (Peronoscleropora Sorghi) For Appropriate Control Strategies (2000)
The study sets out to find the various factors militating against the effective control of the downy mildew disease of maize in some local government areas of Oyo and Ogun States (Nigeria). Lack of adequate communication between the farmers and researchers and the unavailability of downy mildew resistant seeds at the appropriate time and at affordable prices are some of the factors militating against the effective control of the downy mildew disease of maize. The testing of relationships with chi-square between farmers educational levels and incidence of disease shows that there is no relationship between the two i.e. X2 cal > X2 tab at 95% significant level. The chi-square test also indicated that there is still the occurrence of the disease irrespective of whether farmers have access to extension agents or not because X2 cal = 7.98 while X2 tab = 5.99 at 95% significant level. The adoption of an integrated pest management approach, close linkage between the farmers and researchers and the provision of technical advice by extension agents were suggested